Relation between climatic variables and land cover use in the Alto Juruá watershed (Research, Society and Development, 2022)
The use of geotechnology tools has contributed to the understanding of the spatial dynamics of climatic variables and land use in a watershed. This study aimed to evaluate the dynamics of surface temperature, rainfall and evapotranspiration, and their relationship with land use and land cover in the Alto Juruá watershed. The Google Earth Engine (GEE) platform was used for data processing and, through the Code Editor tool, it was possible to program and run a routine to assess surface temperature, rainfall, evapotranspiration, use and land cover and altitude. The average surface temperatures (24.13ºC) increase in the month of july and decrease in the month of september. The average annual temperature is 24.68ºC and the years 2010 and 2016 were the hottest within the studied series. Monthly rainfall averages are 182 mm, with the months of June, July and August being the months with less rain. The average annual rainfall was 1982 mm. The highest surface temperatures are concentrated in the urban center of the Alto Juruá hydrographic basin, with expansion observed over the years coinciding with the expansion of the pasture area.